How Upper/Middle Managers' Ethical Leadership Activates Employee Ethical Behavior? The Role of Organizational Justice Perceptions Among Employees - Al Halbusi, Hussam; Ruiz-Palomino, Pablo; Jimenez-Estevez, Pedro; Gutiérrez-Broncano, Santiago (Frontiers in Psychology, 2021)
Several studies have been conducted on ethical leadership and workplace ethical behavior but little is known about the role of organizational justice and each of its dimensions (procedural, distributive, interpersonal, informational) in this relationship. This study predicts that ethical leadership enhances organizational justice perceptions, including each of its specific dimensions, which in turn enhances employee ethical behavior. The results from two-wave survey data obtained from 270 employees in the Malaysian manufacturing industry confirm that ethical leadership has a positive impact on employee ethical behavior, and that organizational justice and each of its justice dimensions mediate this relationship, both individually and together. Importantly, interpersonal and informational dimensions show the strongest mediation effects. This paper highlights the actions and strategies that can help managers to effectively elevate the moral tone in their organizations. In particular, our findings show where managers must put more emphasis to foster an ethical workplace: on providing fair treatment (interpersonal justice) and honest information (informational justice).